Anthropometric assessment of nutritional status of children attending anganwadi in urban slums of Miraj city, Maharashtra - Gondikar, Abhay; Sangrulkar, Tejaswini V.; Brahmankar, Tanuja R. (International Journal Of Community Medicine And Public Health, 2017)
Background: Children between 1 to 6 years of age in India constitute 15% of total population as against 7% in the developed countries. Nutrition of these children is of prime importance as they are most vulnerable to malnutrition. Anthropometry has become a practical tool for evaluating the nutritional status of children in developing countries which is the best indicator of global wellbeing of children. The objectives were to study nutritional status of study subjects and to identify various socio-demographic risk factors associated with under-nutrition. Methods: This is a cross-sectional study carried out in 205 Children of 0-6 years of age registered in Anganwadis in adopted urban slum area of community medicine department of Government Medical College, Miraj during January –December 2014. Data was collected using a pre-designed proforma and was analyzed at 5% level of statistical significance. For all the classifications in study WHO classifications were used. Results: Out of 205 children, 113 (55.12%) were males and 92 (44.88%) were females. Majority were Hindus (54.1%), from joint family (67.8%), belonged to class IV Socio-economic status, with literate parents (81% fathers and 70.7% mothers), having maternal age between 20-30 years, having birth order one (37.5%), were attending Anganwadi regularly (71.7%), completed their immunization as per age (92.2%). Prevalence of malnutrition was 26.8% (Weight for height or length). 32 (15.6%) children were underweight, 20 (9.8%) children were in MAM i.e. moderate acute malnutrition, and 03 (1.4%) were in SAM i.e. severe acute malnutrition. Prevalence of malnutrition in 166 under 5 children was 72.9 %. 94 (56.6%) children were underweight, 24 (14.5%) children were in MAM, and 03 (1.8%) were in SAM. Prevalence of stunting was 64.5%. Majority children had normal mid arm circumference. Conclusions: Undernutrition was more prevalent in age group of 13-24 months, females, Hindus, class 4 SES, in those having illiterate mothers, in children having birth order one and those with incomplete immunization.